Progress in Origen and the Origenian Tradition - Jacobsen, Anders-Christian; Lettieri, Gaetano; Fallica, Maria (Early Christianity in the Context of Antiquity, 2023)
Progress is a structural and systematic concept in the thought of Origen of Alexandria, which represents one of the most advanced syntheses of the Christian reading of the Old and the New Testaments' legacy and the classical paideia, as well as a rational critique towards every kind of static objectification of the religious. Origen's legacy was capable of radiating its influence through Western theology and philosophy, thus shaping its idea of theological, moral, intellectual, social and political progress. The volume follows the intellectual dynamism generated by the reception of Origen's thought through seventeen articles, which span through the centuries, from the analysis of Origen's thought to its reception history in the Middle Ages, the Renaissance, and the Modern Age, up until the 20th century.